(untitled) (International Conference on Computers in Education, 2017)
Tanaka et al. (2017) developed a system using animation to help children observe the anatomy and behaviors of animals in zoos. A zoo is an informal learning place providing children a chance to observe animals scientifically and systematically. However, most zoos fail to support the observation of animals, and hence there is a need for more research on supporting observation in zoos. Animation is a useful tool to support observation of animal behaviors. The system developed by Tanaka et al. (2017) supported children in noticing not only the outward features and behaviors of animals but also their anatomies and movements. A workshop was held at Kobe Municipal Oji Zoo in Japan, in which children used the system to observe how penguins swim and walk and to note the features of the bones in their legs and flippers. The participants were 19 children, average age 8.1 years (SD = 0.6). In this paper, we examined the percentages of children’s scientific answers to questions incorporated in the prediction, observation, and subsequent interview one month after the workshop. There were four questions on swimming, walking, leg bones, and flipper bones. Each question had three choices. The percentage of scientific answers during prediction, observation, and interview was different for each item. This system was effective for some items, but not for all. In future work, we need to improve the contents and the animations of this system.